Safety of chemotherapy of MDR/XDR-TB patients in high HIV prevalence settings - A. V. Kukurika; E. I. Veselova; L. E. Parolina; O. V. Lovacheva (Туберкулез и болезни лёгких, 2022)
The review used 61 literature sources to discuss 13 publications devoted to safety of treatment of HIV-associated drug-resistant tuberculosis using basic and new regimens of chemotherapy. According to the literature, no additive toxic eﬀects were detected during treatment with anti-tuberculosis and antiretroviral drugs. According to the literature data, no additive toxic eﬀect was found during treatment with anti-tuberculosis and antiretroviral drugs. In conditions of high prevalence of HIV, the pharmacovigilance of drug interactions in combination therapy is particularly relevant since HIV can indirectly increase the number of ADRs not only due to cross-toxicity but also severe immunosuppression, development of immune system recovery syndrome, opportunistic infections, a characteristic intoxication syndrome, a low index body weight and individual characteristics of patients in this category.